Development and validation of the transparency index - Silvia Costa; Ricardo Ferraz; Munira Aminova; Carolina Ferreira; José E. Teixeira; Iain Lindsay; Ana Torres; António J. Silva (Motricidade)
This study aimed to develop and validate the Transparency Index, a tool designed to measure transparency and integrity within sports organisations. The index comprises 15 items across three domains: governance, operational practices, and financial transparency. After expert review, the index underwent content validation and statistical analysis. Descriptive statistics revealed items ranging from 0.02 to 0.88 and standard deviations from 0.14 to 0.5. Reliability analysis showed satisfactory internal consistency (Cronbach’s α = 0.72 for the full index), which improved to 0.74 after removing items 9 and 10 due to their low inter-item correlations. Exploratory factor analysis suggested a four-factor solution, accounting for 56.53% of the variance, with factors representing governance, financial transparency, diversity policies, and collaboration with partners. The Kruskal-Wallis test revealed significant differences between institutional levels (H = 63.29, p < .01), with World and National Federations demonstrating higher transparency scores than Regional Associations. No significant differences were found between evaluators, indicating consistency in scoring. These findings underscore the need for tailored transparency policies across different sports governance levels. The Transparency Index demonstrates potential as a valid and reliable tool for evaluating organisational transparency, with promising applications for enhancing governance practices in sports organisations. Further research is recommended to apply the Transparency Index to a broader sample and refine its dimensions.